1957
DOI: 10.1139/m57-067
|View full text |Cite
|
Sign up to set email alerts
|

A Disease of Grasshoppers Caused by the Bacterium Pseudomonas Aeruginosa (Schroeter) Migula

Abstract: Pse2ldonzonas acrzlginosa is the chief cause of disease in laboratory cultures of grasshoppers. A large number of strains of the bacterium from different localities fell into five types on the basis of reactions with bacteriophages. The five types and their strains were qualitatively similar to one another in morphology, cultural characteristics, and diagnostic biochemical reactions and to a narned culture of P. aeruginosa from the American Type Culture Collection, and their characteristicsagreed with those li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1961
1961
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(17 citation statements)
references
References 12 publications
0
17
0
Order By: Relevance
“…In previous studies, it was reported that P. putida could infect Euproctis chrysorrhoea (Steinhaus, 1963) and Mamestra brassicae (Lepidoptera: Noctuidae) (Ivanov & Gukasjan, 1966). Despite the fact that a number of Pseudomonas species are important insect pathogens, i.e., P. aeruginosa (Bucher & Stephens, 1957;Osborn et al, 2002), P. fluorescens (Krieg, 1961;Lipa & Wiland, 1972;Bucher, 1981;Sezen & Demirbag, 1999, Yaman et al, 1999 and P. chlororaphis (Ivanov & Gukasjan, 1966;Bucher, 1981;Yaman et al, 2002b), P. putida appears insignificant as an insect pathogen (Bucher, 1981;Schneider & Dorn, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, it was reported that P. putida could infect Euproctis chrysorrhoea (Steinhaus, 1963) and Mamestra brassicae (Lepidoptera: Noctuidae) (Ivanov & Gukasjan, 1966). Despite the fact that a number of Pseudomonas species are important insect pathogens, i.e., P. aeruginosa (Bucher & Stephens, 1957;Osborn et al, 2002), P. fluorescens (Krieg, 1961;Lipa & Wiland, 1972;Bucher, 1981;Sezen & Demirbag, 1999, Yaman et al, 1999 and P. chlororaphis (Ivanov & Gukasjan, 1966;Bucher, 1981;Yaman et al, 2002b), P. putida appears insignificant as an insect pathogen (Bucher, 1981;Schneider & Dorn, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…To test this, we used an insect model for P. aeruginosa pathogenesis. We tested the role of QscR in virulence by feeding the mutant and parent to the fruit fly D. melanogaster; a particularly convenient model host among the various insects in which P. aeruginosa causes disease (21)(22)(23). We fed fruit flies with P. aeruginosa cells suspended in a sucrose solution (see Materials and Methods) and monitored the flies for 2 weeks.…”
Section: Regulation Of Quorum-sensing Signal Generator and Signal Recmentioning
confidence: 99%
“…This compound thus could contribute profoundly to the broad pathogenic host range of P. aeruginosa (5,9,36,40,45). It is thought that cyanide inhibition of fungal growth helps account for the suppression of several plant root and leaf fungal diseases (30,68).…”
Section: Vol 183 2001mentioning
confidence: 99%
“…A model for nematode killing based on inhibition of mitochondrial cytochrome oxidase is presented. The action of cyanide helps account for the unusually broad host range of virulence of P. aeruginosa and may contribute to the pathogenesis in opportunistic human infections due to the bacterium.Pseudomonas aeruginosa is a ubiquitous gram-negative bacterium that is virulent towards a wide range of organisms, including bacteria, plants, nematodes, insects, and mammals (5,9,17,19,35,36,41,48,49,62). In humans, P. aeruginosa chronically infects the lungs of most cystic fibrosis patients, causes serious infections of burn wounds and eye lesions, and causes systemic infections of immunocompromised individuals (21,29,33,39).…”
mentioning
confidence: 99%